Micellization, anti-proliferative activity and binding study of cationic gemini surfactants with calf thymus DNA - Wani, Farooq Ahmad; Behera, Kamalakanta; Padder, Rayees Ahmad; Husain, Mohammad; Malik, Maqsood Ahmad; Al-Thabaiti, Nada Shaeel; Ahmad, Rabia; Patel, Rajan (Colloid and interface science communications, 2020)
Aggregation behaviour of two cation gemini surfactants i.e., 1,3-bis (1-decylbenzimidazolium) propane bromide BG10 and 1,3-bis (1-octylbenzimidazolium) propane bromide BG8 was studied using conductivity and dynamic light scattering (DLS). The enthalpy (∆Hmо), entropy (∆Smо) and Gibbs free energy of micellization (∆Gmо) have been observed from the conductivity method at various temperatures. The anti-proliferative potential of these novel gemini surfactants against human non-small lung cancer cell line-H1299 has been investigated. Both gemini surfactants, BG8 and BG10 showed a considerable inhibition in cancer cell proliferation and IC50 values are observed to reduce with chain length. The ctDNA binding was also observed by UV–visible, transmission electron microscopy (TEM), ethidium bromide (EtBr) exclusion experiments, agarose gel electrophoresis, circular dichroism (CD) and viscometry techniques. These results were further validated by in-silico studies. The binding capability of BG surfactants to ctDNA can be observed from their ability to remove EtBr from the intercalating complex of DNA resulting in fluorescence quenching. [Display omitted] •The cation gemini BG8 and BG10 surfactants form aggregates ranging approximately from 100 - 300 nm.•Both BG8 and BG10 showed a significant inhibition in cancer cell proliferation.•The BG surfactants remove EtBr from the intercalating complex of ctDNA resulting fluorescence quenching.